(untitled) (PYC Nepal Journal of Management, 2018)
The study investigates the month-of-the-year effects in Nepalese stock market employing composite index along with other nine sub-indices between mid-July 17, 2007 and mid-July 15, 2017. The study finds statistically significant highest average monthly returns in the month of Ashad (mid-June - mid-July) among other eleven months. On contrary, the significantly negative return is found in the month of Bhadra (mid-August - mid-September). It indicates that the Nepalese stock market has specific returns patterns showing inefficient in weak-form of market efficiency.